The Role of Technology in Primary Health Care Management Strategy : Literature Study - Winanti, Sumi Fitri; Fadillah, Indah; Natasya, Dwi Fanny Amanda; Alwini, An'nisa; Hutagalung, Putri Adinda Ramadani; Raniah, Sofia; Harsana, Amanda Putri; Faiz, Muhammad Nabil; Wasyiem, Wasyiem (Jurnal Kesmas Prima Indonesia, 2025)
Primary health care is a very important first-level service in the health system, especially in remote and low-income areas. The development of digital technology has great potential to improve the effectiveness and efficiency of primary health care through integration in management strategies. This article is a literature study that aims to explore the role of technology in primary health care management strategies based on the results of recent research. Data were obtained from various national and international scientific journals between 2021 and 2025 through searches on databases such as Google Scholar, PubMed, Scopus, and ScienceDirect. The results of the analysis show that the use of technology such as electronic medical records, telemedicine, and mobile health applications can improve access, service quality, and managerial efficiency. However, challenges such as limited infrastructure, digital literacy, and human resource readiness are still major obstacles. This study recommends the need for contextual adaptive strategies to optimize the use of technology in primary health care, especially in developing countries like Indonesia.